Determinants of Inter-Individual Variability in Corticomotor Excitability Induced by Paired Associative Stimulation - Minkova, Lora; Peter, Jessica; Abdulkadir, Ahmed; Schumacher, Lena V.; Kaller, Christoph P.; Nissen, Christoph; Klöppel, Stefan; Lahr, Jacob (Frontiers in Neuroscience, 2019)
Transcranial magnetic stimulation (TMS) is a well-established tool in probing cortical plasticity in vivo. Changes in corticomotor excitability can be induced using a paired associative stimulation (PAS) protocol, in which TMS stimulation over the primary motor cortex is conditioned with an electrical peripheral nerve stimulation of the contralateral hand. PAS with an inter-stimulus interval of 25 ms induces long-term potentiation (LTP)-like effects in cortical excitability. However, the response to a PAS protocol tends to vary substantially across individuals. In this study, we used univariate and multivariate data-driven methods to investigate various previously proposed determinants of inter-individual variability in PAS efficacy, such as demographic, cognitive, clinical, neurophysiological, and neuroimaging measures. Forty-one right-handed participants, comprising 22 patients with amnestic mild cognitive impairment and 19 healthy controls, underwent the PAS protocol. Prior to stimulation, demographic, genetic, clinical, as well as structural and resting-state functional MRI data were acquired. The two groups did not differ in any of the variables, except by global cognitive status. Univariate analysis showed that only 61 % of all participants were classified as PAS responders, irrespective of a group membership. Higher PAS response was associated with lower TMS intensity and with higher resting-state connectivity within the sensorimotor network, but only in responders, as opposed to non-responders. We also found an overall positive correlation between PAS response and structural connectivity within the corticospinal tract, which did not differ between groups. A multivariate random forest (RF) model identified age, gender, education, IQ, global cognitive status, sleep quality, alertness, TMS intensity, genetic factors, and neuroimaging measures (functional and structural connectivity, grey matter volume, and cortical thickness) as poor predictors of PAS response. The model resulted in low accuracy of the RF classifier (58 %; 95% CI: 42% - 74%), with a higher relative importance of brain connectivity measures compared to the other variables. We conclude that PAS variability in our sample was not well explained by factors known to influence PAS efficacy, emphasizing the need for future replication studies.